Factors Affecting the Success of Learning English with Limited Exposure: Reflections from Non-English Department Students - Lubna, Khurniatu Sholikah Qurrotu Aini; Toyyibah, Toyyibah (Journal of Language Intelligence and Culture, 2024)
Acquiring English language skills is an important aspect of education for non-English department students. However, it can be a challenging task, especially for those with limited exposure to the language. This study aims to determine the factors that affect the success of learning English with limited exposure of non-English department students. The subjects of the study were 79 psychology department students. This research used 25 questions followed by open-ended questions and why they chose the options to collect the data. The result showed that motivation was the most factor affecting learning English as much as (80%). The second factor was aptitude and learning strategies which have the same percentage in affecting English learning success that is (76%). The third point that influences learning English success is personality as much as (70%). The last and the lowest factor was learning styles, with a percentage (57%). The result concluded that the students need instrumental motivation in English learning. The students needed the teacher's example and explanation in learning English. The strategy of learning English with medium pressure will help the students in managing their anxiety.